Enhancing Programming Learning through a Smartphone-Based Asynchronous Flipped-Learning Media - Setiawan, Arif; Wahid, Burhanudin Nur; Adhisa, Ryan Rizki (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to develop and evaluate a smartphone-based asynchronous flipped-learning media application called BEST (Belajar Struktur Data) to support programming and algorithm learning in higher education during online learning conditions.Methodology: This research employed a research and development approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The application was implemented with 40 Informatics Engineering Education students at Universitas Muhammadiyah Surakarta. The evaluation involved black-box testing, compatibility testing using Firebase Test Lab, expert validation using Aiken's V from two media experts and one material expert, and usability testing using the System Usability Scale (SUS).Results: The results showed that the BEST application achieved a 100% success rate in functional and compatibility testing. The Aiken's V value obtained from both media and material expert validation was 0.89, indicating that the learning media is valid and feasible. The usability evaluation produced a SUS score of 71.8%, which reflects an acceptable level of usability and high student satisfaction.Applications/Originality/Value: This study contributes an original smartphone-based asynchronous flipped-learning media specifically designed for programming education, offering a practical solution to overcome technical limitations in synchronous online learning and supporting more flexible, independent, and engaging learning experiences in higher education.